Structural Equation Modeling of Service Quality’s Effect on Passenger Satisfaction at New Malang Railway Station - Kawer, Angela Meike; Wicaksono, Achmad; Wicaksono, Agus Dwi (Rekayasa Sipil, 2026)
The increasing number of train passengers in Indonesia requires transportation service providers to continue to improve the quality of their services. This study aims to determine the effect of service quality on train passenger satisfaction at Malang City New Station using the Structural Equation Modeling (SEM) method. Service quality is measured through six primary dimensions: safety, security, reliability, comfort, convenience, and equality. Data is collected through questionnaires distributed to train passengers and analyzed using SEM software. The results indicate that all dimensions of service quality have a significant impact on passenger satisfaction, with the comfort variable exerting the most dominant influence on service quality. The results of testing the hypothesis regarding the Service Quality variable and service user satisfaction at the new Malang City Station yielded a path coefficient of 0.709. The positive direction of the relationship indicates that increased service quality will lead to higher service user satisfaction at the new Malang City Station, with a t-value of 16.387. Since the t value is greater than the t table (1.960) or p (0.000) ? 0.05, then it can be concluded that service quality has a direct and significant influence on service user satisfaction at New Malang Railway Station.